2016
DOI: 10.1097/mbc.0000000000000504
|View full text |Cite
|
Sign up to set email alerts
|

Changes to fibrinolysis in patients with systemic lupus erythematosus are associated with endothelial cell damage and inflammation, but not antiphospholipid antibodies

Abstract: We investigated whether changes to fibrinolysis were associated with other manifestations of systemic lupus erythematosus (SLE), including antiphospholipid (APL) antibody status, endothelial damage, and inflammation. Ninety-four patients (36 SLE patients, 58 healthy controls) were recruited from Tasmania, Australia. Circulating levels of plasminogen, α2-antiplasmin, tissue-type plasminogen activator, plasminogen activator inhibitor-1, and thrombin-activatable fibrinolysis inhibitor (TAFI) were measured, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19] The increased circulating levels of PAP and α2AP, and the impaired fibrinolysis have been reported in patients with SLE. 7,8 These findings suggest that α2AP may play a critical role in the development of SLE.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…[12][13][14][15][16][17][18][19] The increased circulating levels of PAP and α2AP, and the impaired fibrinolysis have been reported in patients with SLE. 7,8 These findings suggest that α2AP may play a critical role in the development of SLE.…”
Section: Introductionmentioning
confidence: 83%
“…Immune deposition, inflammatory responses, hypercoagulability, and thrombosis are associated with LN progression. [5][6][7][8] α2AP not only regulates PAP formation and fibrin deposition through plasmin binding and inhibition but is also associated with the production of several cytokines. 12,18 PAP reportedly induces the production of IgG and IgM in mononuclear cells, 37 and α2AP is associated with the production of IgE and the recruitment of immune cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the specificity and sensitivity of the two tests were different. Some studies 22,23) have reported that fibrinolysis may be associated with inflammation. However, in accordance with the previous study by Girona,7) our study showed no correlations between FDP, EPL, LY30, CL30, and ESR, which indicated inflammation may not play a role in fibrinolysis in patients with TA.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired fibrinolysis is another pathogenic mechanism in SLE, which may help explain why these patients are at increased risk of developing thrombosis (15). Defects in fibrinolysis are related to an increase in the levels of various fibrinolytic inhibitors, such as PAI-1 (16), α2-antiplasmain, TAFI (17), lipoprotein (a) (18), and a decrease of plasminogen activity (17) likely due to anti-plasminogen antibodies (19).…”
Section: Introductionmentioning
confidence: 99%